Analisa Perbandingan Keakuratan Metode Certainty Factor dan Dempster Shafer untuk Diagnosia Dini Penyakit Hepatitis berbasis Mobile - Cynthia Hayat; Amyou Amyou; Marcel Marcel (Journal of Computer Science and Informatics Engineering (J-Cosine), 2020)
Hepatitis is an inflammation of the liver due to a viral infection that attacks and causes damage to cells and the function of the liver. Many methods are currently used in building expert systems, including Certainty Factor and Dempster Shafer. The selection of both Certainty Factor and Dempster Shafer methods is very suitable for expert systems. In the previous study there was the Certainty Factor method used to diagnose hepatitis but there was no accuracy, whereas in Dempster Shafer there was an accuracy rate of 90%. This study aims to find out the suitable method to diagnose hepatitis by comparing the method of Certainty Factor and Dempster Shafer. In this study the application is in the form of a mobile base using Android Studio and database storage with MySQL. After that, do the Application Validation Test with experts and accuracy testing is carried out using samples from expert diagnosis results. The results of the test obtained the accuracy of the test using the Certainty Factor method is 95%. While the accuracy of testing using the Dempster Shafer method is 90%.